Lactate clearance and mortality in pediatric sepsis - Dedi K. Saputra; Ari L. Runtunuwu; Suryadi N. N. Tatura; Jeanette I. Ch. Manoppo; Julius H. Lolombulan (Paediatrica Indonesiana, 2016)
Background Sepsis is a life-threatening condition often encountered in the pediatric intensive care unit. In the last five decades, despite the use of aggressive antibiotics and advances in intensive care medicine, the mortality rate of sepsis remains high. In 2005, the World Health Organization (WHO) estimated that 11 million children die annually due to sepsis, of these, 30,000 children under five years of age die daily. Serum lactate concentration is useful to evaluate the progression of sepsis in children. Lactate clearance can be used to evaluate the outcomes in sepsis management in children.Objective To evaluate the relationship between lactate clearance and patient mortality. We also attempted to assess the usefulness of lactate clearance as an early prognostic marker in pediatric sepsis.Methods This prospective cohort study was conducted at the Pediatrics Department of Prof Kandou General Hospital from November 2013 to April 2014. Consecutive sampling was undertaken on 45 children aged 1 month to 15 years who were diagnosed with sepsis according to the inclusion criteria. First lactate serum was measured immediately following patient admission to the PICU. The next serum lactate measurement was six hours after initial treatment in the PICU.Results The mean lactate clearance was higher in the survivors’ than in the non-survivors’ group (58.48%vs. 18.20%, respectively). Logistic regression analysis revealed a lactate clearance cutoff point of 34.7%, with sensitivity 87.50%, specificity 96.55%, positive predictive value 93.33%, and negative predictive value 93.33%. The formula used was y=1/{1+exp-(4.135-0.119 lactate clearance)}. Chi-square analysis of lactate clearance and mortality revealed an odds ratio (OR) of 196.0 (95%CI 16.34 to 2,351.53; P<0.001).Conclusion Higher lactate clearances significantly associate with lower mortality in children with sepsis.